Isolated digit recognition in Malaysian language - Zainul Abidin Md Sharif,; Masuri Othman,; Tan , Shao Theong (1991)
This paper describes the use of a personal computer to store samples of uttered isolated digit signals and thereupon to recognize the appropriate digit uttered using time domain analysis and template matching. 7he fundamental of linear prediction analysis is briefly introduced and a general description on the hardware and software used in this project is then given. This project is undertaken as an initial step to implement an automatic translation system of daily used keywords terminology in Malaysian to English